On the Need for Collaboration Among NGOs Working for Children's Education Worldwide - (:unkn) unknown (My University, 2023)
This communication, presented at UNESCO Headquarters in Paris during the « Formal Dialogue on the Initiative on the evolving right to education », is based on field experience conducted in Africa, specifically in Côte d’Ivoire. It explores the persistent challenges related to schooling, dropout, and non-schooling of children, highlighting the discrepancies between the principles of the right to education and their actual implementation. Drawing on empirical observations and qualitative surveys carried out with various educational stakeholders (students, families, teachers, local authorities), this contribution advocates for stronger coordination among NGOs working for children's education worldwide. The author proposes the establishment of an inter-NGO collaborative mechanism focused on combating non-schooling, including data sharing, joint initiatives, and coordinated monitoring of progress in each country. Finally, the communication calls for the development of national reports that integrate public policies and contributions from Ministries of Education. The goal is to formulate global conclusions on the effectiveness of the right to education, to foster transnational synergies, and to equip field actors with tools for more structured and effective advocacy.Keywords: Right to education, Non-schooling, NGOs, International cooperation, Children, Africa, Education policies.
Keywords: African Research